Institutional prevention policies and rates of Group B Streptococcus infection among HIV‐infected pregnant women and their infants in Latin America. Issue 2 (20th December 2012) - Joao, Esaú; Gouvea, Maria I.; Freimanis‐Hance, Laura; Cohen, Rachel A.; Read, Jennifer S.; Melo, Victor; Duarte, Geraldo; Ivalo, Silvina; Machado, Daisy M.; Pilotto, Jose; Siberry, George K.; ,
Abstract: Objective: To describe Group B Streptococcus (GBS) prevention policies at 12 Latin American sites participating in the NICHD (Eunice Kennedy Shriver National Institute of Child Health and Human Development) International Site Development Initiative (NISDI) Longitudinal Study in Latin American Countries (LILAC) and to determine rates of rectovaginal colonization and GBS‐related disease among HIV‐infected pregnant women and their infants. Methods: Site surveys were used to assess prevention policies and practices administered cross‐sectionally during 2010. Data collected in NISDI from 2008 to 2010 regarding HIV‐infected pregnant women were used to determine rates of colonization and GBS‐related disease. Results: Of the 9 sites with a GBS prevention policy, 7 performed routine rectovaginal screening for GBS. Of the 401 women included in the NISDI study, 56.9% were at sites that screened. The GBS colonization rate was 8.3% (19/228 women; 95% confidence interval [CI], 5.1%–12.7%). Disease related to GBS occurred in 0.5% of the participants (2/401 women; 95% CI, 0.1%–1.8%); however, no GBS‐related disease was reported among the 398 infants (95% CI, 0.0%–0.9%). Conclusion: Improved efforts to implement prevention policies and continued surveillance for GBS are needed to understand the impact of GBS among HIV‐infected pregnant women and their infants in Latin America.